Utility of Bruton's Tyrosine Kinase Inhibitors in Light Chain Amyloidosis Caused by Lymphoplasmacytic Lymphoma (Waldenström's Macroglobulinemia). (19th January 2022) - Bou Zerdan, Maroun; Valent, Jason; Diacovo, Maria Julia; Theil, Karl; Chaulagain, Chakra P.
Abstract : Of the variety of immunoglobulin related amyloidosis (AL), immunoglobulin M (IgM) related AL represents only 6 to 10% of affected patients, and the majority of these cases are associated with underlying non-Hodgkin's Lymphoma including Waldenström's macroglobulinemia (WM). Ibrutinib, acalabrutinib, and zanubrutinib are Bruton tyrosine kinase (BTK) inhibitors approved for certain indolent B cell non-Hodgkin's lymphoma (NHL). BTK is a nonreceptor kinase involved in B-cell survival, proliferation, and interaction with the microenvironment. We retrospectively evaluated the tolerability and effectiveness of BTK inhibitors ibrutinib and acalabrutinib therapy in ( n = 4) patients with IgM-related AL amyloidosis with underlying WM. Treatment was well tolerated with both hematologic and organ response in patients with AL amyloidosis in the setting of WM. Atrial fibrillation led to the discontinuation of ibrutinib in one patient, and acalabrutinib caused significant thumb hematoma needing dose reduction in another patient. All patients evaluated had the MYD88 mutation. This may explain the good response to BTK inhibitors therapy in our series. BTK inhibitors should be further investigated in larger prospective studies for treatment of AL amyloidosis in patients with lymphoplasmacytic lymphoma/WM.